Precursors and Their Borges: Premodern Sculpting in Modern Time (BEOIBERÍSTICA - Journal of Iberian, Latin American and Comparative Studies (ISSN: 2560-4163 Online), 2024)
Borges is boundless: his texts leave no uncrossed boundaries between distant and close, early and late, medieval and modern. However, such boundlessness is by no means a result of his supposedly morally weightless playfulness, which many postmodernists were glad to see as a worthy harbinger. As I intend to show in this essay, Borges’s main intellectual, literary, and ethical strategy is what might be called time condensation: using his astonishing erudition, Borges shows that our modern and secularized world, where each generation perceives itself as new, unique and unprecedented, is composed of countless strata created by the collective experience of past generations. Borges’s enterprise is consistent with the intellectual and artistic projects of modernism (including the works of Virginia Woolf, Marcel Proust, James Joyce, and Franz Kafka) as it strives to provide an alternative to the linear, irreversible, and secularised time of the modern world; an alternative constructed as a matter of interpretive choice and at the same time a moral and existential choice: to recognize or deny the ethical dimension of time. Jewish ideas played an important, though not the only, role in shaping Borges’s vision of condensed time, as did, more generally, his lifelong sympathetic observation of the unique historical destiny of the Jewish people. Hence, I argue, the formalist tendency in recent scholarship to ‘translate’ Borges’s Jewish theme into a dehistoricized and essentialized language of literary tropes, a sophisticated mind game that bears no relation to actual (Jewish) history, often comes at the cost of turning a blind eye to the ethical dimension of Borges’s intellectual project.